2008
DOI: 10.1007/s12298-008-0024-0
|View full text |Cite
|
Sign up to set email alerts
|

Respiration hastens maturation and lowers yield in rice

Abstract: Role of respiration in plant growth remains an enigma. Growth of meristematic cells, which are not photosynthetic, is entirely driven by endogenous respiration. Does respiration determine growth and size or does it merely burn off the carbon depleting the biomass? We show here that respiration of the germinating rice seed, which is contributed largely by the meristematic cells of the embryo, quantitatively correlates with the dynamics of much of plant growth, starting with the time for germination to the time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 26 publications
(27 reference statements)
1
11
0
Order By: Relevance
“…Germination, which is the most direct means to examine the meristematic behavior, has not been systematically examined as a phenotypic differentiator of any quantitative trait including NUE, despite the evidence that germination rate was tightly correlated with flowering time and yield in rice ( Sitaramam et al, 2008a ). Hence, the present study sought to explore N-responsive differences in germination and used them to identify contrasting rice genotypes that differed in N-responsive yield and therefore NUE.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Germination, which is the most direct means to examine the meristematic behavior, has not been systematically examined as a phenotypic differentiator of any quantitative trait including NUE, despite the evidence that germination rate was tightly correlated with flowering time and yield in rice ( Sitaramam et al, 2008a ). Hence, the present study sought to explore N-responsive differences in germination and used them to identify contrasting rice genotypes that differed in N-responsive yield and therefore NUE.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to the prevailing notion that oxygen consumption (photo oxygen consumption or otherwise) has an opposing influence on yield or is at least a confounding variable as it counteracts the conservation of the photosynthate exclusively toward yield. Sitaramam et al (2008a) showed that meristem is a key determinant in the yield of rice, by demonstrating that the meristematic oxygen consumption hastens the life stages leading to less “time” available for accumulation of the photosynthate. They also showed that fast germinating rice genotypes have higher rates of oxygen consumption and mature faster with lesser grain yield, offering a testable paradigm of the role of energetics in plant yield, under which the role of nitrogen in the process could be studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since no standard remedy exists, we even tested this procedure of uniform sampling in the case of rice seeds by their weight in our earlier studies to predict yield in a single day from the seeds successfully [54]. Clearly, if the procedure is haphazard or without coherence in logic or sampling, the ensuing results would be even worse and it would be the ultimate verdict against the validity of the method.…”
Section: B Test Designmentioning
confidence: 99%